Alterations of the gut virome in patients with systemic lupus erythematosus - Chen, Changming; Yan, Qiulong; Yao, Xueming; Li, Shenghui; Lv, Qingbo; Wang, Guangyang; Zhong, Qin; Tang, Fang; Liu, Zhengqi; Huang, Ying; An, Yang; Zhou, Jing; et al. (Frontiers in Immunology, 2023)
Background: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease that has been linked to the dysbiosis of the gut microbiome and virome. However, the potential characterization of the gut virome in SLE patients needs to be unexplored more extensively. Methods: Herein, we analyzed the gut viral community of 16 SLE patients and 31 healthy controls using both bulk and virus-like particle (VLP)-based metagenomic sequencing of their fecal samples. A total of 15,999 non-redundant viral operational taxonomic units (vOTUs) were identified from the metagenomic assembled contigs and used for gut virome profiling. Results: SLE patients exhibited a significant decrease in gut viral diversity in the bulk metagenome dataset but this change was not significant in the VLP metagenome dataset. Also, considerable alterations of the overall gut virome composition and remarkable changes in the viral family compositions were observed in SLE patients compared with healthy controls, as observed in both two technologies. We identified 408 vOTUs (177 SLE-enriched and 231 control-enriched) with significantly different relative abundances between patients and controls in the bulk virome, and 18 vOTUs (17 SLE-enriched in 1 control-enriched) in the VLP virome. The SLE-enriched vOTUs included numerous Siphoviridae, Microviridae, and crAss-like viruses and were frequently predicted to infect Bacteroides, Parabacteroides, and Ruminococcus_E, while the control-enriched contained numerous members of Siphoviridae and Myoviridae and were predicted to infect Prevotella and Lachnospirales_CAG-274. We explored the correlations between gut viruses and bacteria and found that some Lachnospirales_CAG-274 and Hungatella_A phages may play key roles in the virus-bacterium network. Moreover, we demonstrated the gut viral signatures for disease discrimination and achieved an area under the receiver operator characteristic curve (AUC) of above 0.95, demonstrating the potential of the gut virome in the prediction of SLE. Conclusion: Our ﬁndings revealed the alterations in viral diversity and taxonomic composition of the gut virome of SLE patients. Further studies on the etiology of SLE and the gut viral community will provide new prospects for treating and preventing SLE and other autoimmune diseases.